2019
DOI: 10.1111/jopr.13104
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Clinical Outcomes on Patients Rehabilitated with Complete‐Arch Fixed Implant‐Supported Prostheses According to the Time of Loading

Abstract: Purpose:To perform a systematic review on studies assessing clinical outcomes in patients rehabilitated with complete-arch fixed implant-supported prostheses according to the time of loading. Materials and Methods: Data obtained from patient and clinical outcomes, as implant failure, success rate, survival rate, biological complications, technical complications, mechanical complications, and marginal bone loss, were included on this review. The search was performed on databases PubMed, Scopus, and Cochrane. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 37 publications
(93 reference statements)
0
39
0
4
Order By: Relevance
“…Another traditional option for the rehabilitation of the edentulous mandible is the use of multiple implants in the interforaminal region of the mandible to retain a fixed prosthesis—implant‐supported fixed complete denture (IFCD). The use of four implants ‘ad modum’ Branemark with a permanent fixed rigid cross‐arch suprastructure has been successfully used since the earliest introduction of osseointegrated implants, with high success rates and predictability regarding implant survival 10 and favourable patient‐related outcomes (dPROs) 11 . However, many patients may be reluctant to be submitted to this type of treatment, due to the more complex and invasive surgical procedures, and since this treatment modality generates an additional cost due to the more extensive surgical procedure with a higher number of implants, prosthetic components, aftercare and laboratory steps, as well as the need for additional measures for oral hygiene 12 …”
Section: Introductionmentioning
confidence: 99%
“…Another traditional option for the rehabilitation of the edentulous mandible is the use of multiple implants in the interforaminal region of the mandible to retain a fixed prosthesis—implant‐supported fixed complete denture (IFCD). The use of four implants ‘ad modum’ Branemark with a permanent fixed rigid cross‐arch suprastructure has been successfully used since the earliest introduction of osseointegrated implants, with high success rates and predictability regarding implant survival 10 and favourable patient‐related outcomes (dPROs) 11 . However, many patients may be reluctant to be submitted to this type of treatment, due to the more complex and invasive surgical procedures, and since this treatment modality generates an additional cost due to the more extensive surgical procedure with a higher number of implants, prosthetic components, aftercare and laboratory steps, as well as the need for additional measures for oral hygiene 12 …”
Section: Introductionmentioning
confidence: 99%
“…Dental implants have several important advantages such as improved mastication efficiency and restoration of aesthetics and have become common prosthetic methods for dental treatment. Furthermore, several studies have reported high implant success and survival rates ( 13 ). Dental implant treatment is a highly reliable treatment; however, despite the low incidence of implant failure, failures occur occasionally, even with expert dentists.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, seven did not make clear how many reviewers participated in the study selection and data collection [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. Only eight reviews did not make any restrictions on the language [ 3 , 9 , 10 , 12 , [15] , [16] , [17] , [18] ], and the rest included practically only articles in English. Virtually all systematic reviews included randomized or non-randomized clinical trials, but some prospective studies were also included [ 10 , [18] , [19] , [20] , [21] , [22] ].…”
Section: Resultsmentioning
confidence: 99%